2023
DOI: 10.3390/mi15010082
|View full text |Cite
|
Sign up to set email alerts
|

Advancement in Biosensor Technologies of 2D MaterialIntegrated with Cellulose—Physical Properties

Ghazaleh Ramezani,
Ion Stiharu,
Theo G. M. van de Ven
et al.

Abstract: This review paper provides an in-depth analysis of recent advancements in integrating two-dimensional (2D) materials with cellulose to enhance biosensing technology. The incorporation of 2D materials such as graphene and transition metal dichalcogenides, along with nanocellulose, improves the sensitivity, stability, and flexibility of biosensors. Practical applications of these advanced biosensors are explored in fields like medical diagnostics and environmental monitoring. This innovative approach is driving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 143 publications
0
1
0
Order By: Relevance
“…A study on cellulose-acetate-based composites used as coatings for biodegradable magnesium implants for trauma showed promising results. The composite coating reduced the biodegradation rate of the magnesium implants, known to promote bone healing and exhibit adequate mechanical strength during their biodegradation in the bone-healing process [101]. Another study on Mg-Ca-Zn biodegradable alloys used as orthopedic implants demonstrated high biocompatibility and excellent mechanical properties, making them suitable for small bones of the feet and hands, ankles, or small joints [102,103].…”
Section: • Biodegradable Medical Implantsmentioning
confidence: 99%
“…A study on cellulose-acetate-based composites used as coatings for biodegradable magnesium implants for trauma showed promising results. The composite coating reduced the biodegradation rate of the magnesium implants, known to promote bone healing and exhibit adequate mechanical strength during their biodegradation in the bone-healing process [101]. Another study on Mg-Ca-Zn biodegradable alloys used as orthopedic implants demonstrated high biocompatibility and excellent mechanical properties, making them suitable for small bones of the feet and hands, ankles, or small joints [102,103].…”
Section: • Biodegradable Medical Implantsmentioning
confidence: 99%